Currículo e educação física: processo em construção para a escola pública. - Santos, Damião Oliveira (2009)
The present study one inserts in the research line New Technologies, Education and Work of the Nucleus of After-Graduation in Education of the Federal University of Sergipe has for objective to analyze the process of construction of the Proposal Curricular of Physical Education of the State Secretary of Education of Sergipe, being considered itself the objective and subjective questions that decided the elaboration of the cited document. One is about a case study that has as base theoretician-methodology of the dialectic historical materialism that has as empirical field the Regional Direction of Education of Aracaju (DEA). For in such a way, we use the analysis of contents and interview half-structuralized with two groups of citizens: 04 representative professors of the SEED and 06 teachers who if found in regency of classroom at the moment of the elaboration of the document. We search with this research, from the elements of the curricular theory, to point of that he forms the resume served/serves as an important ally in the materialization of the principles and values of the ideological estimated ones of the neoliberal politics. In this direction, the process of elaboration of the curricular proposals, to the light of the neoliberalism, consists as vehicle that legitimizes to the options politics and the ideological apparatus them related. Thus, we contract that the constant occurred changes of Government of 1996, moment where implementation of the Law nº 9,394/96 of Lines of direction and Bases of the Education up to 1997 year of publication of the Proposal Curricular of Physical Education of the State Secretary of Education had been substantial so that in the weakness of the process of construction of the Proposal Curricular of Physical Education of the State Secretary of Education; in all the analyzed documents we observe a plurality of conceptions. This determination of the State Secretary of Education, with our agreement, intervened significantly for the sprouting of epistemological incoherencies that had harmed the theoretical recital of the Proposal. /Education. We also evidence that in the process of elaboration of the related document the participation of the professors was substantially small, limiting it election and organization of the contents. When using different conceptions, the Proposal Curricular of Physical Education of the State Secretariat of Education of Sergipe, possess an epistemological fragility that harms the understanding of the Physical Education. Thus, only from a critical formation marked out with buoys in one to make pedagogical freedom, a Proposal Curricular will be able to assist in the construction of a society more human and joust.